Anti-CCP: History and its Usefulness - M. Herold; V. Boeser; E. Russe; W. Klotz (Clinical and Developmental Immunology)
Antibodies directed to cyclic citrullinated peptides (anti-CCP) are highly specific for rheumatoid arthritis (RA) and can easily be detected in sera by using commercially available immunoassays. The second version of the anti-CCP test (anti-CCP2) demonstrated high specificity (89-98%) and good sensitivity (41-88%) for RA. Commercially available ELISA methods from three different companies are on the market. All three CCP2 assays show similar results as all CCP2 assays use the same antigen-coated plates. This study was an evaluation of a new automated method for the determination of anti-CCP2 in a routine laboratory setting. Five hundred and fourty three serum samples were tested for anti-CCP2 within normal routine diagnostic using a commercially available ELISA and retested with a prelaunch version of a new and fully-automated method (EliA™). The results were comparable. The new automated assay is easy to use and demonstrated a diagnostic sensitivity of 80% and specificity of 97%.